SUBTITLING ANALYSIS OF HANSEL AND GRETEL: WITCH HUNTER - Anggraeni, Triasmi (JoLLIET, 2016)
This research emphasized on scrutinizing the subtitling strategy used by thesubtitler of Hansel and Gretel Witch Hunter movie by Jack and the Wilee. Italso analyses the subtitling quality of Hansel and Gretel Witch Hunter movie byJack and the Wilee. This research is descriptive qualitative research. Thepurposes of this research are: (1) To describe the subtitling strategies used bythe subtitler of Hansel and Gretel Witch Hunter movie by Jack and the Wilee,and (2) To describe the subtitling quality of Hansel and Gretel Witch Huntermovie by Jack and the Wilee. The data are analyzed based on the theories ofsubtitling strategies and subtitling quality. The data are utterances containingsubtitling strategies and subtitling quality collected from the data source. Thedata source is the subtitle of Hansel and Gretel Witch Hunter movie by Jack andthe Wilee. The results of this research show that there are 748 data. Theresearcher finds nine strategies are: (1) 226 data to transfer, (2) 20 data toexpansion, (3) 156 data to paraphrase, (4) 11 data to condensation, (5) 8 data todecimation, (6) 62 data to imitation strategy, (7) 3 data to transcription strategy,(8) 372 data to deletion strategy, (9) 7 data to resignation. There is nodislocation strategy. There are three aspects for good quality that subtitlingshould fulfill: accuracy, acceptability, and readability: (1) 599 data or 80 %accurately, (2) 67 data or 9 %less accurately, (3) 82 data or 11 % inaccurately,(4) 622 data or 83.2 % acceptability, (5) 67 data or 9 %less acceptability, (6) 59data or 7.8 % unacceptability, (7) 631 data or 84.3 %high readability level, (8)56 data or 7.5 % moderate readability level, and (9) 61 data or 8.2 % lowreadability level.Key words: movie, quality, strategy, subtitling